Having skin in the game: How players purchase representation in games. (December 2022) - Reza, Alia; Chu, Sabrina; Nedd, Adanna; Gardner, Daniel
Microtransactions are a relatively new feature of video game software involving the purchase of in-game items, often using real money. Players may use these transactions to purchase in-game advantages, or cosmetic features such as 'skins', which change the way a player's avatar looks without influencing gameplay mechanics. Skins may be an opportunity for developers to offer – and players to purchase – alternative demographic appearances. In this article we examine some of the potential costs associated with skins beyond their price tag, especially those felt by players of color, given a normative – free – white default. While previous research has looked at player identity, representation in gaming media and players' purchasing practices individually, few scholars have looked at the intersection between all three. We analyze this intersection within the practices of selling and purchasing skins in games. We distributed a survey through social media and to gaming communities online and analyzed 158 responses. We identify quantitative differences in responses of participants of color and White participants, such as participants of color spending more on average than white participants on skins in the games they play. We discuss qualitative themes we describe as quasi-acceptance and privileged allyship, that build on previous literature about how players of color interact with – and may feel resigned about – representation in games.